PENGARUH TRANSPARANSI PENGELOLAAN KEUANGAN DANA DESA DAN PEMBERDAYAAN MASYARAKAT TERHADAP KESEJAHTERAAN MASYARAKAT DESA SIDOHARJO - Dewi Kusuma Wardani; Ratih Ranika Putri Utami (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to determine the effect of transparency in financial management of village funds and community empowerment on community welfare in Sidoharjo Village, Tepus District, Gunungkidul Regency. This research method uses quantitative descriptive methods and primary data using questionnaires. This study took a sample of residents who were divided into 11 hamlets in Sidoharjo Village, Tepus District, Gunung kidul Regency. The sampling technique is stratified random sampling. Data collection is done by distributing questionnaires directly to Peoples homes, attending social gatherings and routine meetings held by community members. It aims to obtain more data from respondents directly. The number of questionnaires processed was 120 questionnaires. Data were analyzed using multiple linear regression analysis. The results of this study indicate that community empowerment has a positive effect on the welfare of the people of Sidoharjo Village, Tepus District, Gunungkidul Regency, while transparency in financial management of village funds does not affect the welfare of the community in Sidoharjo Village, Tepus District, Gunungkidul Regency.